La influencia del factor liderazgo para fomentar la adopción de la nueva cultura organizacional de la empresa minera Hochschild - Zanella Giurfa, Jazmín (2022)
In early 2019, Hochschild Mining began a process of cultural transformation through which innovation was included as a new cultural attribute. Since the leaders are the main promoters of culture within the organizations, one of their main challenges is to promote the adoption of this new attribute. Therefore, the objective of this research is to assess the correlation between the applied leadership style and the adoption of the company´s new culture. The research was based on two main theories: the theory of the Full Range Leadership Model by Bass and Avolio and the organizational culture model by Denison. Based on Bass and Avolio's theory, it is proposed as hypothesis that the transformational leadership style has a positive relationship with the adoption of the new attribute of innovation, specifically the dimension of intellectual stimulation, since different sources also relate knowledge management with innovation. A descriptive-correlational quantitative approach was used, and information was collected through a questionnaire on a sample of 115 workers from the corporate offices. Based on the results, it was identified that not only intellectual stimulation but also the other dimensions of the transformational leadership style are related to the characteristics of an innovative organizational culture. Therefore, it is concluded that this is the ideal leadership style to promote cultural transformation in the case of Hochschild Mining.